Methods for evaluating error correcting codes based on a compound channel model - Suematsu, Toshinari; Imai, Hideki (Electronics & communications in Japan. Part 1, Communications, 1986)
Since error correcting and detecting codes are used in many fields, the assessment of the code performance in actual communication environments is an important subject. A communication channel is expressed by a statistical model and the assessment is usually done by simulation and/or analysis method. However, conventional assessment methods are insufficient from the viewpoint of ease of handling, precision, etc. In this paper we present new methods for evaluating error‐correcting and error‐detecting codes. These evaluations make use of a new compound channel model which represents actual channels better than the channel models proposed previously. An exact analysis is used for computing the performances of codes. For these reasons, we can obtain reliable results. The time required for the evaluation is relatively small. Furthermore, their adaptability to various channels and codes is high and they are easy to use. Methods of evaluating the double encoding scheme, a well‐known scheme in CIRC, is also presented. Finally, some examples of evaluating codes by these methods are presented and their effectiveness is shown.